Analisis Hukum Terhadap Perjanjian Hutang Piutang dengan Jasa Kalampa Piti di Kota/Kabupaten Bima - Wirawan, A. Rachmat; Komuna, Avelyn Pingkan; Robiansyah, Anton (Alauddin Law Development Journal (ALDEV), 2023)
The practice of debt receivables was used as a means to get income from giving debts with excess from the moment of return which became known as loan sharks. In Bima City, the practice of loan sharking became known as the "kalampa piti" system or silencing money from loans. The law in Indonesia itself does not prohibit interest in every lending and borrowing transaction. This can be seen in article 1754 BW which is also strengthened in article 1765 BW which allows interest in every lending transaction. However, the problem is the process of agreeing on debt receivables agreements based on verbal statements without a written agreement that causes conflicts between kalampa piti parties and customers in the form of physical, psychic violence to the seizure of valuables. For this reason, it is necessary to have concrete procedures to ensure legal certainty and protection for the parties.